The Powers of Death: Recognition, Resistance, Resurrection - Jason Goroncy (Jurnal Jaffray, 2021)
This essay is an invitation to examine the powers of death, particularly the modes by which such powers are manifested in the world, modes that relate to but are irreducible to an individual’s life. It considers contributions to the subject from Karl Barth, Walter Wink, and William Stringfellow, among others, to argue that while death and its associated powers are pervasive, they are also penultimate realities. The powers of death meet their end in Jesus Christ. The gospel concerning Jesus Christ is the invitation to live as if such a claim were true, to recognise one for whom death is not the foreign territory and in whom death is confronted and its powers brought to nought. It is the invitation to a life in which resistance to the powers of death is possible. It is the invitation to live a life characterised by resurrection.